A five-coordinate Ni(i) complex supported by 1, 4, 7-triisopropyl-1, 4, 7-triazacyclononane. Issue 53 (16th June 2022) - Griego, Leonel; Woods, Toby J.; Mirica, Liviu M.
Abstract : We report the synthesis and characterization of an uncommon five-coordinate Ni(i ) complex supported by 1, 4, 7-triisopropyl-1, 4, 7-triazacyclononane. Abstract : An isolated Ni(ii )-nitrosyl complex supported by the bulky tridentate 1, 4, 7-triisopropyl-1, 4, 7-triazacyclononane (iPr3 TACN) ligand was obtained from the reaction of a Ni(ii ) dimethyl complex with NOPF6, suggesting the in situ formation of a Ni(i ) species that reacts with the resulting NO product. Use of a π-acceptor ancillary isocyanide ligand led to the isolation and characterization of an uncommon 5-coordinate Ni(i ) complex supported by the iPr3 TACN ligand and tert -butylisocyanide.